Explicit dynamic modelling of architectural glazing subject to blast loading - Michael Seica (Challenging Glass Conference, 2016)
The response of an architectural glazing panel to dynamic loading, such as that from explosions, is analysed using an explicit dynamic finite element algorithm coded into a computer program. This software allows for the simulation of various glazing types, and is capable of predicting displacements and stresses up to cracking of the glass and the hazard level experienced by occupants. A variety of support conditions are available, along with several methods of specifying the blast load. Details and challenges of the numerical algorithm and coding are presented, together with the verification procedure that was performed through comparisons with results from analyses using general-purpose finite element programs and from available literature. In parallel, experimentation was performed to determine the dynamic mechanical properties of glass by testing the material in a Split Hopkinson Pressure Bar.